Invariance principle for one class of Markov chains with fast Poisson time. Estimate for the rate of convergence - Baev, A. V.; Bondarev, B. V.; Баев, А. В.; Бондарев, Б. В.; Баев, А. В.; Бондарев, Б. В. (Institute of Mathematics, NAS of Ukraine, 2006)
We obtain an estimate for the rate of convergence of normalized Poisson sums of random variables determined by the first-order autoregression procedure to a family of Wiener processes.